Which elements were significant in reducing obstetric anal sphincter injury? A prospective follow-up study - Ole Bredahl Rasmussen; Annika Yding; Charlotte Sander Andersen; Jane Boris; Finn Friis Lauszus (BMC, 2021)
Abstract Background To examine which elements of an obstetric anal sphincter injury (OASI) care bundle were protective for OASI. Several interventional trials showed that application of a care bundle involving a hands-on approach to perineal protection may reduce the risk of OASI. Previously, we found that only the element "hand on the fetal head" in itself was protective, although the risk of a type 2 error was calculated to be 50%. Methods A prospective follow-up study in an obstetric department in Denmark with 3200 deliveries per year. We included a cohort of 10,383 women giving birth vaginally from gestational week 22 + 0 from 2016 through 2019. We documented on a person-level the five elements of the care bundle together with maternal and obstetrical characteristics. The elements were 1) communication, 2) visible perineum, 3) hand on fetal head, 4) perineal support and 5) certification. Regression analysis was used for analysis of associations. The primary outcome measure was OASI. Results The total rate of OASI in vaginally delivering women was 1.9%. The incidence was 3.2% in nulliparous women giving birth vaginally. The rate of cesarean section was 16.5% and for episiotomy 2.4%. The reduction in the incidence of OASI was sustained since 2013. Hand on the fetal head and perineal support both were protective factors for OASI. In case of a nulliparous woman with a neonate weighing 3500 g giving birth spontaneously, the relative risk (RR) for OASI was 0.50 (95% CI 0.49- 0.51) with use of hand on the fetal head together with perineal support against no use. Similarly, with a nulliparous woman giving birth to a neonate of 3500 g by vacuum extraction, the RR for OASI was 0.65 (95% CI 0.62-0.68) against no use. Conclusions Both hand on the fetal head and perineal support were associated with a reduced risk of OASI.